Regional analysis of in-situ harvesting potential for expansion in Sub-Saharan Africa - Ag Water Solutions, Inc. (International Water Management Institute, 2012)
Sub-Saharan Africa (SSA) faces great challenges in development, including the highest poverty rate in the world, food insecurity, and malnutrition. Given that agriculture is the single most important source of rural livelihood in Africa, an agricultural growth strategy will go a long way to reducing hunger and poverty on the subcontinent. Among the numerous challenges to enhancing agricultural production in SSA is the large spatial and temporal variability and availability of water resources. Currently, agriculture in SSA is predominantly rainfed. The limited access to water in arid areas or during dry seasons and drought spells often presents restrictions to farming and to improving agricultural productivity. Therefore, enhanced agricultural water management has often been regarded as a promising solution to boost levels of agricultural productivity in SSA.